Goosebumps- Go eat worms! - Stine, R. L. (New York, Scholastic Inc., 2024)
"Todd loves his basement worm farm. Worms are fascinating creatures--it's just a convenient bonus that they happen to gross out his family. But when Todd starts to find worms in unlikely and unwanted places--like his bed, his toothbrush, and his spaghetti--the tables have turned. Now Todd is the one running scared!"